Analisis Faktor-Faktor Yang Dipertimbangkan Dalam Penentuan Nisbah Bagi Hasil Atas Pembiayaan Mudharabah Pada Perbankan Syariah (Studi Empiris Pada Perbankan Syariah Kota Samarinda) - Amir Hidayat; Fatahul Rahman (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
This study aims to; determine the factors considered by Islamic Banking as shahibul maal in determining the profit sharing ratio up of financing; determine the factors most taken into consideration by the Islamic Banking as shahibul maal in the determination of the profit sharing ratio on financing mudaraba. This study used a population of 75 people consisting of management and employees in five Islamic Bank in the city of Samarinda, the Syariah BRI, BNI Syariah, Bank Syariah Mandiri, Bank Syariah Muamalat and Bank of East Kalimantan. The research instrument used in the form of a questionnaire. Validity and reliabiltas instrument was tested using Spearman rank and Cronbach alpha. Data were analyzed using factor analysis with the aid of a computer program Statistical Product and Service Solution (SPSSversi 11.0 forWindows). Results showed: (1) based on the calculation on the total variance explained is known that the number of factors that have eigenvalues > 1 of 7 factors, namely the customer's business, guarantees, regulation, policy banks, costs, competition and risks. Seventh these factors into consideration in determining the ratio of Islamic Banking for the top results of financing, (2) based on the calculation of the total variance explained is known that the factors that have the greatest eigen values that 5.923 is a factor of the customer's business. Thus the most dominant factor into consideration Islamic Banking in determining the profit sharing ratio of financing is a factor on the customer's business